Effect of organic selenium and omega-3 fatty acids on performance, antioxidant status and fatty acid composition of meat in broiler chickens - KUMAR, P; TIWARI, S P; SAHU, TARINI; GENDLEY, M K; NAIK, SURENDRA KUMAR (The Indian Journal of Animal Sciences, 2015)
A 2 x 3 factorial experiment was conducted to evaluate the effect of adding selenomethionine (0 and 0.3 ppm) and omega-3 fatty acid (0, 0.5 and 1% of diet) on performance, blood antioxidant capacity and fatty acid composition of meat in broiler chickens. The study was conducted using broiler chicks (180) that were assigned to 1 of the 6 dietary treatments. The significant interactions were observed between selenomethionine and omega-3 fatty acids for growth performance, dressing percentage, selenium and omega-3 fatty acids composition of meat, serum antibody titer against Newcastle disease and the lymphoid organ weights. The chickens with the highest body weight and dressing percentage were fed 0.3 ppm of selenomethionine with 0.5% of omega-3 fatty acid. The lowest fat value was found in the broilers that were fed 0.5% omega-3 fatty acid. Dietary selenomethionine significantly increased the selenium content of meat. The glutathione peroxidase (GPx) activity and thiobarbituric acid (TBA) value of muscle significantly increased as the levels of selenium and fat source increased in the diet. The highest serum antibody titer against Newcastle disease was recorded in chickens that were fed the highest levels of selenium and fat source. Thus it may be speculated that selenomethionine and omega-3 fatty acid enriched broilers diet improved growth performance, antioxidant status and meat composition.